ZFD 10: Zbornik radova s Međunarodnoga znanstvenog skupa Zadarski filološki dani 10 održanog u Zadru 10. studenoga 2023. - ompadmin; Šušić, Mirela; Radčenko, Marina (2026)
The proceedings of the Zadar Philological Days 10 bring together papers presented at the International Scientific Conference Zadar Philological Days 10, held at the University of Zadar on November 10, 2023, organized by the Department of Croatian Studies and the Department of Russian Studies of the University of Zadar. It was the jubilee, twentieth year of the Zadar Philological Days, which are held biennially, and which have traditionally brought together numerous prominent domestic and foreign scholars. The conference was attended by more than fifty scholars from Croatia and abroad (Austria, Spain, Poland, Slovakia, Bulgaria, Serbia, etc.), and included five thematic units: "Miroslav Krleža (130th Anniversary of Birth)", "Contemporary Readings of Slavic Literature", "Active Tendencies in Contemporary Slavic Languages", "Language and Literature in a Contemporary Methodological Context" and "Zadar - Art, Culture, Literature". The collection contains thirteen scientific papers that have undergone double-blind peer review, and the entire collection has also been peer reviewed by two reviewers. The papers are arranged within thematic units within which they were presented at the philological conference.
Keywords: phraseology; cryopoetics; Slavic drama and theatre; poetic discourse; Croatian language; Croatian as a foreign language; Miroslav Krleža; polemical strategies; pragmatic particles; academic writing; literary anthropology